ASSESSING ECOLOGICAL RESILIENCE OF INDONESIAN CORAL REEFS - Imam Bachtiar; Ario Damar; Suharsono .; Neviaty P. Zamani (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Ecological resilience is an important property of natural ecosystem to be understood in coral reef management. Resilience of Indonesian coral reefs was assessed using 2009 COREMAP data. The assessment used 698 data of line intercept transects collected from 15 districts and 4 marine physiographies. Resilience index used in the assessment was developed by the authors but will be published elsewhere. The results showed that coral reefs at western region had higher average resilience indices than eastern region, and Sunda Shelf reefs had higher resilience indices than coral reefs at Indian Ocean, Sulawesi-Flores, or Sahul Shelf. Four districts were found to have coral reefs with highest resilience indices, i.e. Bintan and Natuna (western region), and Wakatobi and Buton (eastern region). Raja Ampat had coral reefs with lower average resilience indices than that of Wakatobi. Uses of resilience index in coral reef management should be coupled with other information such as maximum depth of coral communities.